Пушкин - Тынянов Юрий Николаевич (Писатели о писателях, 1984)
Экземпляры: Нефтебазинская библиотека (20070809) / Инвентарный номер: 11709z1 / Сис.шифр: Р2 / Авт.знак: Т 93 / ГРНТИ: 17 / ББК: 84 (2 Рос=Рус)6